Risk Management Analysis On The School Activity Plan And Budget Application Information System (ARKAS) Using Cobit 2019 - Fernandes Gamaliel, Adhi; Firmansyah, Gerry; Mulyo Widodo, Agung; Tjahjono, Budi (Asian Journal of Social and Humanities, 2024)
In the era of globalization and the advancement of information technology, the application of information technology is an important need for educational institutions, including schools. This research focuses on the implementation of the School Activity Plan and Budget Application Information System (ARKAS) at the Palu Safety Center Christian Vocational School to increase efficiency and effectiveness in planning and managing school activities and budgets. However, the implementation of ARKAS is inseparable from various risks that can affect the effectiveness and success of the system. Therefore, risk management analysis is essential to ensure that all potential risks can be identified, analyzed, and minimized. This study uses the COBIT 2019 framework to manage risks in the application of information technology in schools. The study identifies challenges such as resistance to change, resource limitations, and information security risks. This study aims to explore how the implementation of ARKAS in the Palu Safety Army Christian Vocational School can be optimized through risk management analysis using the COBIT 2019 framework. The results of the study show that the use of COBIT 2019 can help in identifying and managing risks effectively, so that the implementation of ARKAS can run more efficiently and transparently. The resulting recommendations are expected to improve the quality of school budget management and become a reference for other schools that face similar challenges in the application of information technology.